In Data We Trust? Comparison of Electronic Versus Manual Abstraction of Antimicrobial Prescribing Quality Metrics for Hospitalized Veterans With Pneumonia. Issue 7 (July 2018) - Jones, Barbara E.; Haroldsen, Candace; Madaras-Kelly, Karl; Goetz, Matthew B.; Ying, Jian; Sauer, Brian; Jones, Makoto M.; Leecaster, Molly; Greene, Tom; Fridkin, Scott K.; Neuhauser, Melinda M.; Samore, Matthew H.
Abstract : Background: Electronic health records provide the opportunity to assess system-wide quality measures. Veterans Affairs Pharmacy Benefits Management Center for Medication Safety uses medication use evaluation (MUE) through manual review of the electronic health records. Objective: To compare an electronic MUE approach versus human/manual review for extraction of antibiotic use (choice and duration) and severity metrics. Research Design: Retrospective. Subjects: Hospitalizations for uncomplicated pneumonia occurring during 2013 at 30 Veterans Affairs facilities. Measures: We compared summary statistics, individual hospitalization-level agreement, facility-level consistency, and patterns of variation between electronic and manual MUE for initial severity, antibiotic choice, daily clinical stability, and antibiotic duration. Results: Among 2004 hospitalizations, electronic and manual abstraction methods showed high individual hospitalization-level agreement for initial severity measures (agreement=86%–98%, κ=0.5–0.82), antibiotic choice (agreement=89%–100%, κ=0.70–0.94), and facility-level consistency for empiric antibiotic choice (anti-MRSA r =0.97, P <0.001; antipseudomonal r =0.95, P <0.001) and therapy duration ( r =0.77, P <0.001) but lower facility-level consistency for days to clinical stability ( r =0.52, P =0.006) or excessive duration of therapy ( r =0.55, P =0.005). Both methods identified widespread facility-level variation in antibiotic choice, but we found additional variation in manual estimation of excessive antibiotic duration and initial illness severity. Conclusions: Electronic and manual MUE agreed well for illness severity, antibiotic choice, and duration of therapy in pneumonia at both the individual and facility levels. Manual MUE showed additional reviewer-level variation in estimation of initial illness severity and excessive antibiotic use. Electronic MUE allows for reliable, scalable tracking of national patterns of antimicrobial use, enabling the examination of system-wide interventions to improve quality. Abstract : Supplemental Digital Content is available in the text.